Whales sing - Harris, Caroline, 1964- (London : Kingfisher, 2006)
Simple text and color photographs introduce the characteristics and habits of whales and dolphins.
Includes index.
4.3
K-3.
K-3
Keywords: Cetacea -- Juvenile literature; Dolphins -- Juvenile literature; Whales -- Juvenile literature; Dolphins; Whales; Dolphins; Whales